Value Model For Text Mining - Thyagarajan, K; Nanthini, R (International Journal of Computer Sciences and Engineering, 2025)
Data Retrieval can be characterized as the movement of acquiring data or information significant to data needs from a gathering of data assets. In like manner, Resources are accessible in colossal, huge and unstructured. From the accessible Resources, just a section or some is needed by the clients. Hence some algorithm has to be derived to carry out this retrieving process. There are many previously proposed algorithms. Almost they are unique in nature of implementing the retrieving process. Many algorithms retrieve information based on term similarity where the result is not quite accurate to the user need. Here in this newly proposed algorithm called “Value Model for Text Mining (VM)” the Information retrieving process is performed based on semantic similarity. Hence this algorithm results in better performance in retrieving more related information by ranking the terms in the Fuzzy set.